2011
DOI: 10.1177/1469540510391365
|View full text |Cite
|
Sign up to set email alerts
|

Methodological challenges in using practice theory in consumption research. Examples from a study on handling nutritional contestations of food consumption

Abstract: In this article, we discuss the challenges of analytical translations between practice theory and empirical research methods in consumption research. We argue that a social constructivist interpretation of practice theory can be particularly useful in enabling consumption researchers to carry out empirical studies that are different from mainstream approaches to consumer culture. Such mainstream approaches typically privilege either individual consumer choices or cultural structures outside of the reach of con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
140
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 217 publications
(145 citation statements)
references
References 57 publications
1
140
0
4
Order By: Relevance
“…It also complements the work of other authors who have taken a practice-based approach to food-related health issues (e.g. Delormier, Frohlich, & Potvin, 2009;Halkier & Jensen, 2011;Meah, 2014;Milne, 2011;. We argue that practice-based approaches are of considerable value in understanding vulnerability and are less likely than other approaches to 'blame the victim' for failing to follow official guidance, providing an alternative understanding of the reasons why people engage in behaviours that may increase their vulnerability to specific threats (cf.…”
Section: Current Approachesmentioning
confidence: 62%
See 1 more Smart Citation
“…It also complements the work of other authors who have taken a practice-based approach to food-related health issues (e.g. Delormier, Frohlich, & Potvin, 2009;Halkier & Jensen, 2011;Meah, 2014;Milne, 2011;. We argue that practice-based approaches are of considerable value in understanding vulnerability and are less likely than other approaches to 'blame the victim' for failing to follow official guidance, providing an alternative understanding of the reasons why people engage in behaviours that may increase their vulnerability to specific threats (cf.…”
Section: Current Approachesmentioning
confidence: 62%
“…As outlined by Reckwitz (2002) and applied by Warde (2005Warde ( , 2016, practice theorists are united in their argument that social practices should be the focus of analysis rather than individuals (who are the 'carriers' of practices) or social structures (that only exist as a result of the sedimentation of social practices over time) (cf. Halkier & Jensen, 2011). Practice theorists, such as Schatzki (2002), have emphasised the inseparability of 'doings and sayings' in the analysis of social life, and this concern with situated action has led to increased interest in ethnographic observation of everyday life alongside attitudinal research or studies of reported behaviour.…”
Section: Theory and Methodsmentioning
confidence: 99%
“…With a focus on doings and sayings, emergent design, and a holistic approach, the ethnographic method (Arnould & Wallendorf, 1994;Crang & Cook, 2007;Hammersley & Atkinson, 2007;Moisander & Valtonen, 2006) has been argued to be well suited for studies influenced by practice theory (Halkier & Jensen, 2011;Korkman, 2006). The attention to detail; the combination of interviews, observations, and collections; and the analysis of textual and nontextual artefacts allows researchers to examine and illustrate (some of) the complexities of heterogeneous practices involving meanings, competences, and materials.…”
Section: Methodsmentioning
confidence: 99%
“…As well as practices directly associated with provisioning and eating, these include practices which in some way have a bearing on food consumption, such as work practices, care practices, travel practices and so on (e.g. Halkier & Jensen, 2011;Warde, 2016). Food consumption events may be situated within (potentially concurrent) 'meta-practices' enacted via a skein of interdependent practices, such as mothering (Molander, 2011), 'critical consumption' (Bellotti & Mora, 2016) and 'ethical' or 'environmental' food consumption (Fonte, 2013).…”
Section: Food and Social Practicesmentioning
confidence: 99%